Code-switching in Middle English healing charms - Letizia Vezzosi (Filologia Germanica)
Medieval discursive healing charms share a lot of features with medical recipes, in that both charms and recipes generally have the same organizational structure, entail “rituals”, have an oral and a written component, use foreign words, prayers and formulas, and both aim to cure diseases or to prevent perils. However, intuitively, charms do not coincide with recipes. The present paper intends to analyse the use of foreign words in Middle English healing charms, in particular, whether language shift involves simple nouns or verbs, or verbal or noun phrases or whether they coincide with clause units, in which external structural component of the charm it occurs and what functional role(s) language shift plays. The study will mainly concentrate on Latin shift and show that some generalisations about code-switching in Middle English healing charms are possible, and significant for their categorization as a separate text-type from medical remedies. In fact, unlike medical remedies, code switching in healing charms occurs as formulaic language and in ritual formulas, which are those two features that place them closer to prayers.